2015
DOI: 10.5812/ijp.386
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Using Amplatzer Ductal Occluder for Transcatheter Closure of Perimembranous Ventricular Septal Defect in Pediatrics

Abstract: Background:Perimembranous Ventricular Septal Defect (PMVSD) is the most common subtype of ventricular septal defects. Transcatheter closure of PMVSD is a challenging procedure in management of moderate or large defects.Objectives:The purpose of this study was to show that transcatheter closure of perimembranous ventricular septal defect with Amplatzer Ductal Occluder (ADO) is an effective and safe method.Patients and Methods:Between April 2012 and April 2013, 28 patients underwent percutaneous closure of PMVSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Generally, pmVSD closure using either the Duct Occluders or the VSD Coil does not eliminate the risk of CHB as well as other major complications. However, the rate of this complication in our study was low and comparable to the CHB rate of surgical closure documented in the literate …”
Section: Discussionsupporting
confidence: 84%
“…Generally, pmVSD closure using either the Duct Occluders or the VSD Coil does not eliminate the risk of CHB as well as other major complications. However, the rate of this complication in our study was low and comparable to the CHB rate of surgical closure documented in the literate …”
Section: Discussionsupporting
confidence: 84%
“…El Said et al [23] proposed three different locations for measurement of the defect: at the left ventricular opening of the VSD; at the largest diameter of the aneurysm, usually in the midsegment of the aneurysm; and at the right ventricular opening of the VSD aneurysm, usually the smallest diameter of the defect, where they proposed the use of a device 2 mm larger than this last measurement. Ghaderian et al [25] proposed to select an ADO device at least 2 mm larger than the narrowest of the measured VSD diameter in right side by ventriculogram. As mentioned previously, we measured the narrowest portion of the VSD on the left ventricular side during the diastolic left ventricular angiogram, and the devices were chosen not to exceed this diameter by 2 mm in case of using ADO device; and in case of using ADO II, the central disc was chosen not to exceed this measure by 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…El-Sisi et al [26] in a prospective observational single center study of 30 patients reported a 100% success using ADO devices (I and II). Ghaderian et al [25] used an ADO device in 28 patients with a successful rate of 96.4%. Hua et al [27] published a 100% successful closure of PmVSD in 16 patients using AVP II.…”
Section: Discussionmentioning
confidence: 99%
“… 8) 9) 10) As a result, there are important modifications for the prevention of CAVB, and various positive clinical experiences have since been reported with those devices. 11) 12) In Korea, there was a report about transcatheter closure of perimembranous VSD with an Amplatzer duct occluder I, 1) but it was an off-label use of the device. Recently, various types of Cocoon occluders (Vascular Innovations Co., Nonthaburi, Thailand) for VSD were developed.…”
Section: Introductionmentioning
confidence: 99%